Metabolic Control - Herzig, Stephan (Springer International Publishing Imprint: Springer, 2016)
1 Central nervous system control of metabolism -- 2 Glucocorticoids and metabolic control -- 3 Anti-lipidemic drugs -- 4 Genomics and metabolism -- 5 cAMP signaling -- 6 cGMP and brown adipose tissue -- 7 Inflammatory signaling and metabolism -- 8 Insulin signaling -- 9 Nuclear receptor co-factors in metabolism -- 10 Novel treatment options in diabetes -- 11 Adipose tissue stem cells -- 12 Adipokines -- 13 Immune cells and metabolism -- 14 Brown adipose tissue in humans -- 15 Diabetes and Cancer -- 16 Cancer Cell Metabolism -- 17 Incretins
Description based upon print version of record
Keywords: Kontrolle; Stoffwechsel